Differential treatment of individuals with mental health conditions in high-consequence decision-making: a comparison of policy on advance directives and assisted suicide in three European countries - Gloeckler, Sophie; Scholten, Matthé; Biller-Andorno, Nikola (Frontiers in Psychiatry, 2025)
While both assisted suicide and advance directives relate to potentially high-consequence decision-making, the procedures for assisted suicide requests and expressing preferences through an advance directive typically place such processes outside of acute, emergency scenarios. These contexts allow for the decisions to be well-considered. As such, assisted suicide for individuals with mental health conditions and psychiatric advance directives present two valuable cases to examine how well-considered preferences with potentially high consequences are treated. The following study compares policies regarding assisted suicide and advance directives in Switzerland, the Netherlands, and Germany, highlighting policy distinctions between psychiatric and nonpsychiatric cases. By analyzing the implications of these various regulatory frameworks, the paper’s aim is to support well-founded legal and clinical practice across jurisdictions with attention to potentially discriminatory practices. All three jurisdictions create conditions whereby those with mental health conditions can, theoretically, access assisted suicide. In all three jurisdictions, treatment refusals expressed in advance directives for non-psychiatric care are binding, even if such refusals may be life-limiting, but the three jurisdictions handle the risk a person can assume through an advance directive in psychiatric cases quite differently from one another. The overarching regulatory differences found can be summarized as 1) a high degree of deference to clinician judgment in Switzerland, 2) arguments founded on the clinician’s duties to patients in the Netherlands, and 3) recognition of inviolable rights that apply uniformly to all in Germany; each has different implications when it comes to the rights of those with mental health conditions. Countries can use these findings toward a critical review of the policies that define respect for well-considered, high-consequence decisions, avoiding unjustified differential treatment of those with mental health conditions.